Similarity Amidst Diversity: Lessons about Women Representation from Pati and Demak - Tawakkal, George Towar Ikbal; Utaminingsih, Alifiulahtin; Garner, Andrew D.; Wike, Wike; Seitz, Thomas R.; Putra, Fadillah (Political Science Program, Universitas Negeri Semarang, 2021)
While the focus of most research in women's politics has been on the number of legislative seats and explaining the under-representation of women and other marginalized groups, we argue that there also needs to be a greater focus on voters themselves and their attitudes about gender representation in Indonesia. We focus on three broad series of questions. First, gender differences in attitudes about women candidates precisely. Second, gender differences in policy priorities. Third, gender differences in attitudes about one specific aspect of Indonesian elections – money politics or what is sometimes referred to as